2021
DOI: 10.1111/1758-2229.12990
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic and metatranscriptomic analysis reveals enrichment for xenobiotic‐degrading bacterial specialists and xenobiotic‐degrading genes in a Canadian Prairie two‐cell biobed system

Abstract: Summary Biobeds are agriculture‐based bioremediation tools used to safely contain and microbially degrade on‐farm pesticide waste and rinsate, thereby reducing the negative environmental impacts associated with pesticide use. While these engineered ecosystems demonstrate efficient pesticide removal, the microbiomes in these environments remain largely understudied both taxonomically and functionally. This study used metagenomic and metatranscriptomic techniques to characterize the microbial community in a two‐… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…After metagenomic analysis of the activated sludge sample, a total of 68 subtypes of pesticide-degrading genes were identified, and out of them, dhn gene (encode dehydrogenase and degrade metamitron) was found to be dominant. Pesticide contaminates the metagenomic analysis of soil sample, revealing that as the concentration of pesticide increases in the soil, the expression and number of pesticide-biodegrading genes also increases and are mostly peroxidase, monooxydase, and cytochrome P450 (Russell et al, 2021). Hence, these studies confirmed that high-throughput techniques have enough potential to examine the microbial community and their different powerful pesticide-degrading genes under complex environments.…”
Section: Introductionmentioning
confidence: 63%
“…After metagenomic analysis of the activated sludge sample, a total of 68 subtypes of pesticide-degrading genes were identified, and out of them, dhn gene (encode dehydrogenase and degrade metamitron) was found to be dominant. Pesticide contaminates the metagenomic analysis of soil sample, revealing that as the concentration of pesticide increases in the soil, the expression and number of pesticide-biodegrading genes also increases and are mostly peroxidase, monooxydase, and cytochrome P450 (Russell et al, 2021). Hence, these studies confirmed that high-throughput techniques have enough potential to examine the microbial community and their different powerful pesticide-degrading genes under complex environments.…”
Section: Introductionmentioning
confidence: 63%
“…In a similar study, Góngora-Echeverría et al (2018) [108] identified several archaea (23), bacteria (598), and fungi (64) species in lab-scale biobed systems with the presence of a mixture of commercial pesticide formulates (2,4-D, atrazine, carbofuran, diazinon, and glyphosate). In addition, Russell et al (2021) [109] evaluated the bacterial diversity in a two-cell biobed system. After the treatment of pesticide residues, in cell one, 81 bacterial species from 58 genera were identified, while in cell two, 36 bacterial species from 33 genera were identified.…”
Section: Microorganismsmentioning
confidence: 99%
“…Hence, new culture-independent approaches such as metagenomics are gaining momentum to identify non-cultivable microbes with xenobiotic degradation potential [68,69]. Few relevant xenobiotic degrading microorganisms were identified with culture-independent approaches, such as Sphingopyxis, Afipia, Oligotropha, Rhodopseudomonas, Mesorhizobium, and Stenotrophomonas [70]. The dominance of Thalassolituus and Oleispira have also been identified as vital oil-degrading bacteria through metagenomics and the metatranscriptomic approach [71].…”
Section: Omics Approaches To Combat Xenobiotic Pollutionmentioning
confidence: 99%
“…They observed the upregulation of oxidase, hydrolase and NADPH-cytochrome P450 reductase genes for hydrolysis, oxidation and dealkylation of phoxim. Metatranscriptomic analysis of a two-cell Canadian biobed system identified diverse xenobiotic-degrading bacterial phyla such as Sphingopyxis, Mesorhizobium, Oligotropha, Stenotrophomonas, Afipia and Pseudomonas having an important role in the degradation of xenobiotics [70].…”
Section: Transcriptomics and Metatranscriptomicsmentioning
confidence: 99%